Use of antibiotics in a Cienfuegos municipality population - Diana Rosa Fernández Ruiz; Zaida Pérez Meneses; Olga Lidia Cuevas Pérez; Maira Quirós Enríquez; Belkis Barrios Romero; Yeni Dueñas Pérez (Medisur)
Background: the use of antibiotics is frequently excessive and inappropriate, which can produce adverse effects. Objective: to characterize the use of antibiotics in the Cienfuegos municipality urban population. Methods: an exploratory, retrospective study was carried out in which 164 people over 18 years of age were surveyed and this survey was applied with the following variables to study: sociodemographic characteristics; If you used antibiotics in the last six months, who prescribed or suggested it, drug used, disease against which you took it, when did you stop taking them, if you had self-medication habits and knowledge about the negative consequences of such actions. Results: The 148 people (90, 2%) declared having used antibiotics in the last six months, the drug that they most reported consuming was amoxacillin (29, 7%); Tonsillitis (31.7%) was the main condition that motivated the use of antibiotics and the moment the patient stopped taking it was when he was advised by his doctor (66.2%). The highest percentage of use was by medical prescription (75.7%); the 23.7% self-medicated and the people who did it the most were female (71.4%) and with a level between pre-university (34.3%) and university (51.4%). Conclusions: the high consumption of antibiotics, their use in viral infections, self-medication and unfulfillment with the indicated treatment are irrational practices, which contribute to increase the negative effects of antibiotics, for which it is necessary to expand the informative campaigns, aimed at the modification of these behaviors in the population and in the health staff in charge of prescribing these drugs.